2017
DOI: 10.1080/0167482x.2017.1334051
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression in adolescent mothers

Abstract: There is limited literature addressing adolescent postpartum depression, but there has been a significant growth of interest in recent years. There is a need for more randomized control trials to establish gold standards for assessing postpartum depression in adolescent mothers and standards for treatment in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 59 publications
5
49
0
2
Order By: Relevance
“…While there is a paucity of research exploring the unique factors implicated in adolescent PPD, there are currently five published reviews summarising between 9 and 40 studies of 'risk factors' associated with adolescent peripartum depression. The culmination of these reviews has suggested associations between several psychosocial variables and increased PPD symptoms, which include family conflict (Reid & Meadows-Oliver, 2007), interpersonal factors, perceived parental competence, coping (Kleiber and Dimidjian, 2014), maternal childhood experiences, body satisfaction (Siegel & Brandon, 2014), substance use and trauma history (Dinwiddie et al, 2017), prior depression, and a history of abuse (Recto & Champion, 2017).…”
Section: Current Limitations For Identifying Risk Factors Specific Tomentioning
confidence: 99%
See 1 more Smart Citation
“…While there is a paucity of research exploring the unique factors implicated in adolescent PPD, there are currently five published reviews summarising between 9 and 40 studies of 'risk factors' associated with adolescent peripartum depression. The culmination of these reviews has suggested associations between several psychosocial variables and increased PPD symptoms, which include family conflict (Reid & Meadows-Oliver, 2007), interpersonal factors, perceived parental competence, coping (Kleiber and Dimidjian, 2014), maternal childhood experiences, body satisfaction (Siegel & Brandon, 2014), substance use and trauma history (Dinwiddie et al, 2017), prior depression, and a history of abuse (Recto & Champion, 2017).…”
Section: Current Limitations For Identifying Risk Factors Specific Tomentioning
confidence: 99%
“…Furthermore, selection effects into the intervention/programme may be present. Another limitation of the aforementioned reviews is the potential of publication bias in not having included unpublished literature in their reviews (Reid & Meadows-Oliver, 2007;Dinwiddie et al, 2017). The inclusion of participants up to the age of 21, an age-range which has been cited in the literature as 'young adults' (Milan et al, 2007), may also affect the generalisability of conclusions to 'adolescent' populations exclusively (Recto & Champion, 2017;Siegel & Brandon, 2014).…”
Section: Current Limitations For Identifying Risk Factors Specific Tomentioning
confidence: 99%
“…Approximately 95% of all births to girls under age 18 occur in low-and middle -income countries (LMICs), where supporting infrastructure for healthcare is limited (UNFPA, 2013). Perinatal depression (PD), occurring during pregnancy and in the year postpartum, is common among adolescent mothers than older mothers of childbearing age [4,24]. The occurrence of PD among adolescents complicates their unique age-and development-related challenges and thus demands services attuned to the unique needs of this age group.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping physically active during pregnancy is associated with improved mental wellbeing (Haakstad et al, 2016). Given the high rates of mental health problems in pregnant teenagers, emphasising that physical activity might improve subjective sense of wellbeing may be important (Dinwiddie et al, 2018). The current NICE guidelines apply to teenagers and recommend at least 30 minutes per day of moderate intensity activity, characterised as activity that leads to faster breathing, increased heart rate and feeling warmer, for example walking at 3-4 mph (National Institute for Health and Care Excellence, 2010).…”
Section: Physical Activity and Sedentary Behaviourmentioning
confidence: 99%